The Effect of 7P Marketing Mix on The Satisfaction of Foreign Tourists at Siloam Hospital Denpasar - Nyoman Adhi Pratama; Denpharanto Agung Krisprimandoyo (Publikasi Indonesia, 2026)
This research examines how the seven elements of the marketing mix product, price, place, promotion, people, process, and physical evidence, collectively known as the 7Ps shape the satisfaction levels of overseas patients seeking treatment at Siloam Hospital Denpasar, Bali. It is driven by the expanding medical tourism sector on the island and the growing rivalry among hospitals competing for foreign patients. A cross-sectional, quantitative approach was applied, drawing on a purposively selected group of international visitors who used outpatient or inpatient services during 2026. A closed-ended, Likert-scale questionnaire, already verified for validity and reliability, was used to gather the data, which were subsequently processed through multiple linear regression. Findings indicate that the 7P marketing mix, taken together, exerts a significant influence on patient satisfaction, supported by comparatively strong R and R Square figures. Examined individually, people, process, and physical evidence each contribute positively and significantly to satisfaction, with physical evidence emerging as the most influential, trailed by people and then process, whereas product, price, and promotion show no significant contribution and place exerts a negative one. Overall, the results suggest that within a medical tourism setting, strengthening the hospital’s physical surroundings, the caliber of its staff, and the smoothness of its service procedures ought to be treated as priorities for raising satisfaction among international patients.